2015
DOI: 10.1016/j.molp.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

SKIP Confers Osmotic Tolerance during Salt Stress by Controlling Alternative Gene Splicing in Arabidopsis

Abstract: Deciphering the mechanisms underlying plant responses to abiotic stress is key for improving plant stress resistance. Much is known about the regulation of gene expression in response to salt stress at the transcriptional level; however, little is known about this process at the posttranscriptional level. Recently, we demonstrated that SKIP is a component of spliceosome that interacts with clock gene pre-mRNAs and is essential for regulating their alternative splicing and mRNA maturation. In this study, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
159
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(165 citation statements)
references
References 62 publications
(111 reference statements)
6
159
0
Order By: Relevance
“…In plants, we previously reported that SKIP interacts with ELF7, a core component of the Paf1 complex (Paf1c) (He et al ., ), to form the SKIP‐ELF7, which activates the transcription of FLC and MAF1‐5 and represses the floral transition in Arabidopsis (Cao et al ., ; Y. Li et al ., ). We also confirmed that SKIP is a component of the spliceosome, and that it is required for the genome‐wide splicing of pre‐mRNAs and proper functioning of the circadian clock and abiotic stress response in Arabidopsis via the regulated splicing of clock‐ and stress tolerance‐related genes (Wang et al ., ; Feng et al ., ; Y. Li et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, we previously reported that SKIP interacts with ELF7, a core component of the Paf1 complex (Paf1c) (He et al ., ), to form the SKIP‐ELF7, which activates the transcription of FLC and MAF1‐5 and represses the floral transition in Arabidopsis (Cao et al ., ; Y. Li et al ., ). We also confirmed that SKIP is a component of the spliceosome, and that it is required for the genome‐wide splicing of pre‐mRNAs and proper functioning of the circadian clock and abiotic stress response in Arabidopsis via the regulated splicing of clock‐ and stress tolerance‐related genes (Wang et al ., ; Feng et al ., ; Y. Li et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SR45 has been found to interact with three U5 small nuclear ribonucleoprotein proteins (Zhang et al, 2014) as well as with several other Arabidopsis SR proteins, namely, SCL33, RSZ21, SR30, SR34, and SR34a (Golovkin and Reddy, 1999;Zhang et al, 2014;Stankovic et al, 2016). Two other reported SR45-interacting proteins in Arabidopsis are the spliceosomal component SKIP (Wang et al, 2012), which confers salt stress tolerance (Feng et al, 2015), and CACTIN, an essential nuclear factor required for embryogenesis (Baldwin et al, 2013). Early studies had shown that AFC2, a LAMMER-type protein kinase, is able to interact with and phosphorylate SR45 in vitro (Golovkin and Reddy, 1999) and found SR45 to be confined to the nucleus, either diffusely distributed in the nucleoplasm or concentrated in speckles, with its subnuclear dynamics being regulated by phosphorylation, ATP, and transcription (Ali et al, 2003;Ali and Reddy, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Here, the results showed that although expression of VvPMA1 α was higher than VvPMA1 β expression in root, regardless of treatment (Figures 7A,B), the expression level of VvPMA1 β still greatly increased under salt stress, suggesting that alternative splicing of VvPMA1 was markedly induced under salt conditions. Previous results showed that splicing factors, such as serine/arginine-rich (SR), Ski-interacting protein (SKIP) etc., can control the AS of pre-mRNAs encoded by salt tolerance genes under salt stress in plants (Syed et al, 2012; Feng et al, 2015) and different growth conditions can modulate gene expression or protein modification of splicing factors causing dynamic changes in the splicing factor profile, further impacting expression of target genes. So we supposed that the expression of spliced variant VvPMA1 β must be controlled by one or some specific splicing factors in grape root under salt conditions, moreover, VvPMA1 β expression maintained low level in root under salt stress probably because the specific splicing factor has weak activity.…”
Section: Discussionmentioning
confidence: 99%